1994
DOI: 10.1021/es00062a026
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dehalogenation of Hexachloroethane, Carbon Tetrachloride, and Bromoform by Anthrahydroquinone Disulfonate and Humic Acid

Abstract: The reductive dehalogenation of hexachloroethane (CzCLj), carbon tetrachloride (CC14), and bromoform (CHBr3) was examined at 50 "C in aqueous solutions containing either (1) 500 pM of 2,6-anthrahydroquinone disulfonate (AHQDS), (2) 250 pM Fe2+, or (3) 250 pM HS-. The pH ranged from 4.5 to 11.5 for AHQDS solutions and was 7.2 in the Fez+ solutions and 7.8 in the HS-solutions. The observed disappearance of C&16 in the presence of AHQDS was pseudo-first-order and fit k'ccb = ko[A(OH)zI + kdA(0H)O-I + kz[A(O)~~-l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
200
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(211 citation statements)
references
References 46 publications
8
200
2
Order By: Relevance
“…AQDS is a widely used model ETM for environmental and contaminant redox transformations of diverse type (Curtis and Reinhard, 1994;Borch et al, 2005;Bhushan et al, 2006;Finneran, 2006, 2008;Zhang et al, 2007). AQDS is a synthetic three-ring quinone with structural analogy to quinone groups in humic substances (Curtis and Reinhard, 1994), and to biogenic quinones (Nurmi and Tratnyek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…AQDS is a widely used model ETM for environmental and contaminant redox transformations of diverse type (Curtis and Reinhard, 1994;Borch et al, 2005;Bhushan et al, 2006;Finneran, 2006, 2008;Zhang et al, 2007). AQDS is a synthetic three-ring quinone with structural analogy to quinone groups in humic substances (Curtis and Reinhard, 1994), and to biogenic quinones (Nurmi and Tratnyek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This can have a major effect on the migration and toxicity of many of these compounds (14). It is thought that the redox-reactive components of HS that are involved in these reactions are the quinone moieties (20,21,28).Although HS are ubiquitous, they were always considered inert refractory organic material, especially in anoxic environments. Recent research, however, has demonstrated that HS can in fact play an important role as electron sinks for anaerobic respiratory bacteria and fermentative bacteria, stimulating mineralization of complex organic carbon compounds in the * Corresponding author.…”
mentioning
confidence: 99%
“…HS are redox-active compounds and can reduce metals with estimated reduction potentials of 0.5 to 0.7 eV (45). They have been demonstrated to transfer electrons from reduced inorganics (sulfide) and organics (ascorbic acid) to various heavy metals, nitroaromatics, and chlorinated solvents (3,20,21,26,37,41,43,45,48). This can have a major effect on the migration and toxicity of many of these compounds (14).…”
mentioning
confidence: 99%
“…Reduction of AQDS to AHDS was monitored with UV/vis spectroscopy, and a noticeable shift could be seen after bubbling hydrogen gas in the presence of our Pd catalyst. As a preliminary test, of the effectiveness of this reduction method, we decided to use our reduced AHDS to replicate previous studies showing the reduction of hexachloroethane (HCA) to PCE in the presence of AHDS (Curtis and Reinhard, 1994). This experiment was conducted in reactors sealed with only Teflon-coated rubber septa, and, as expected we observed the reduction of HCA to PCE ( Figure 20).…”
Section: Natural Organic Mattermentioning
confidence: 75%